Foreign Ownership, Free Cash Flow, and Assets Utilization of Manufacturing Industry - Nurna Aziza; C Rafflesiantono S (Universitas Negeri Semarang, 2022)
Purpose : This study aims to examine the effect of moderating role of foreign ownership in the relationship between net profit margin and free cash flow on assets utilization in Indonesian manufacturing companies. Method : Net profit margin and free cash flow act as independent variables while assets utilization is the dependent variable and foreign ownership is the moderating variable. The research sample was determined using a purposive sampling approach with several criteria as the basis for determining it. Observations in this study were conducted from 2018 to 2020, manufacturing companies listed on the Indonesian Stock Exchange were the focus of this study. 36 companies were selected as samples with 108 observations. Testing the research hypothesis was conducted by using Moderated Regression Analysis (MRA). Findings : The results of the tests showed that asset utilization was positively and significantly impacted by Net Profit Margin and Free Cash Flow. Additionally, foreign ownership was insignificant in strengthening the effect of net profit margin and free cash flow on asset utilization. Novelty : The study specifically focused on foreign ownership, while previous research was based on structure ownership as a whole. Keywords : Assets Utilization; Foreign Ownership; Free Cash Flow; Net Profit Margin